Review Of Muhammad Asad's Works “Sahih Al-Bukhari The Early Years Of Islam - Amir, Ahmad Nabil (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
This paper discusses Muhammad Asad’s (1990-1992) seminal work Sahih al-Bukhari The Early Years of Islam that wasfirst published in 1935 by The Arafat Publications, Srinagar, Kashmir and its second impression in 1981 by Dar Al-Andalus, Gibraltar. It presents modern translation and commentary of Sahih al-Bukhari, which brought forth significance philosophy and principle of hadith commentary in modern context. The paper aims to analyse the essential ideas developed by Muhammad Asad in his discussion of hadith and compared this with other critical works set forth by classical and contemporary Muslim traditionists. The research was structured based on descriptive, analytical, historical and comparative method. The study concluded that the work was momentous and profound reflecting contextualist approach in expounding the meaning of hadith and its intrinsic philosophy and far-reaching social and spiritual implication. It set forth crucial and highly influential methods of commentary of al-Bukhari’s Sahih – Sahih al-Bukhari The Early Years of Islam that had immensely contributed to the revival of hadith tradition and commentary (sharh) in modern ages.